2022
DOI: 10.3390/biomedicines10123077
|View full text |Cite
|
Sign up to set email alerts
|

Do Psychological Factors Influence the Elastic Properties of Soft Tissue in Subjects with Fibromyalgia? A Cross-Sectional Observational Study

Abstract: Nowadays, there is evidence related to the impact that psychological factors have on symptoms, specifically vegetative ones, and on the autonomic nervous system in patients with fibromyalgia (FM). However, there are no studies to correlate the level of association between psychological factors and the elastic properties of tissue in the FM population. Elastic properties of soft tissue reflect age- and disease-related changes in the mechanical functions of soft tissue, and mechanical failure has a profound impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In this regard, our results showed similar values when assessing SEL in healthy plantar fascia; nevertheless, the level of association between PF elasticity and thickness was very low. If this relationship were found, it would be of great interest to both clinicians and researchers since the loss of elasticity indicates disease progression and/or the effects of non-successful aging [35]. Although the presented results showed no relationship between PF elasticity and thickness, further studies should analyze this not only in healthy subjects, but also in those suffering from chronic PF pain.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this regard, our results showed similar values when assessing SEL in healthy plantar fascia; nevertheless, the level of association between PF elasticity and thickness was very low. If this relationship were found, it would be of great interest to both clinicians and researchers since the loss of elasticity indicates disease progression and/or the effects of non-successful aging [35]. Although the presented results showed no relationship between PF elasticity and thickness, further studies should analyze this not only in healthy subjects, but also in those suffering from chronic PF pain.…”
Section: Discussionmentioning
confidence: 75%
“…Although the presented results showed no relationship between PF elasticity and thickness, further studies should analyze this not only in healthy subjects, but also in those suffering from chronic PF pain. In this line, current studies have found a relationship between elastic properties of tissue and alterations in the autonomic nervous system [35,36]. This is only a hypothesis and more studies in this line are needed.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, the elastic properties of soft tissue, as well as cartilaginous tissues, are influenced or even determined by the activity of the sympathetic nervous system 19 . In patients with FM, a relationship between psychological factors and the elasticity of tissues has been shown 20 , as well as with sympathetic nervous system dysfunction 21 , however, little research has been carried out to study elastic properties in tender or MTrp, and the existing results are not yet conclusive. Therefore, there is a need for research to assess such painful points to better understand the relationship between tissue elasticity and pain pressure thresholds (PPT), since SEL can be employed to measure the elastic properties of soft tissue, and a decrease in elasticity indicates the progression of disease and/or the effects of unsuccessful aging 21 23 .…”
Section: Introductionmentioning
confidence: 99%